2015
DOI: 10.1016/j.jneumeth.2014.07.020
|View full text |Cite
|
Sign up to set email alerts
|

A system and method to interface with multiple groups of axons in several fascicles of peripheral nerves

Abstract: Background Several neural interface technologies that stimulate and/or record from groups of axons have been developed. The longitudinal intrafascicular electrode (LIFE) is a fine wire that can provide access to a discrete population of axons within a peripheral nerve fascicle. Some applications require, or would benefit greatly from, technology that could provide access to multiple discrete sites in several fascicles. New Method The distributed intrafascicular multi-electrode (DIME) lead was developed to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 41 publications
0
24
0
Order By: Relevance
“…Furthermore, the distributed intra-fascicular multielectrode (DIME), an evolution of LIFE, is designed in order to access multiple fascicles within a nerve. For the aim of providing more selectivity, it is composed of multiple LIFEs with their proximal ends coiled in a sheath to provide robustness and facilitate implantation [93]. Another study proposed a 15electrode array lead that trifurcates into three groups of five LIFEs, and showed that it had sufficient mechanical fatigue resistance.…”
Section: Intra-fascicular Electrodesmentioning
confidence: 99%
“…Furthermore, the distributed intra-fascicular multielectrode (DIME), an evolution of LIFE, is designed in order to access multiple fascicles within a nerve. For the aim of providing more selectivity, it is composed of multiple LIFEs with their proximal ends coiled in a sheath to provide robustness and facilitate implantation [93]. Another study proposed a 15electrode array lead that trifurcates into three groups of five LIFEs, and showed that it had sufficient mechanical fatigue resistance.…”
Section: Intra-fascicular Electrodesmentioning
confidence: 99%
“…The longitudinal orientation, which aligns the fine wire with the nerve fibers, further reduces the potential for mechanical stress-induced damage or movement. It is possible to place multiple LIFEs in one fascicle, in different fascicles within one nerve or in multiple nerves to provide access to multiple sites that are distributed in a region of the body [50]. The length of the exposed region, which is designed to be approximately equivalent to internodal spacing (1 mm), increases the likelihood of proximity to a node; the longitudinal placement, which aligns the exposed region parallel to the fibers, minimizes the number of fibers in close proximity.…”
Section: Intrafascicular Electrodes: Stimulationmentioning
confidence: 99%
“…Since the electrodes must be placed within a fascicle, insertion requires a more detailed and lengthy surgical procedure [50,56]. Both the insertion procedure and long-term presence within the fascicle present risks of trauma to the nerve fibers and neighboring tissue [53].…”
Section: Intrafascicular Electrodes: Stimulationmentioning
confidence: 99%
“…invasive penetrates the perineurium to place components inside the fascicle. Examples include the Longitudinal IntraFascicular Electrode (LIFE) [97,98], Transverse Intrafascicular Multichannel Electrode (TIME) [99] and Utah Slanted Electrode Array [100].…”
Section: Physical Interactionmentioning
confidence: 99%